Lithium-sulfur battery electrode process
The formation of the sulfur anode with a porous shell structure through the dry mixing method solves the problems of low availability, insufficient rate capability and poor cycle stability in the charging and discharging process of the lithium sulfur anode, and achieves high cycle performance and long-life battery performance.
Patent Information
- Application Number
- JP2024559311
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-07
- Filing Date
- 2023-04-06
- Publication Date
- 2025-04-16
AI Technical Summary
The zinc-sulfur anode of existing lithium sulfur batteries has problems such as low availability, insufficient rate capability, poor cycle stability and capacity attenuation during the charging and discharging process. The complex synthesis method leads to high manufacturing costs, and it is difficult to effectively replicate the complex structure after multiple charging and discharging, resulting in unavoidable capacity loss.
The sulfur particles and the binder are dried by dry mixing. After adding a carbon source, contacting the solvent to form an anode colloid, and then removing the solvent to form a sulfur anode with a porous shell structure. This method provides sufficient exposure to sulfur particles and mechanical adaptability by controlling the solubility of the adhesive in the solvent.
The high circulation performance and long life of the lithium sulfur battery anode are achieved. By forming sulfur particles with a porous shell structure, the rapid delivery ability of lithium ions is enhanced, the volume expansion of sulfur is adapted to sulfur, the dissolution of soluble polysulfides and the passage of electrolytes is reduced, and the circulation stability and capacity retention rate of the battery is significantly improved.
Smart Images

Figure 2025511808000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application, filed under the Patent Cooperation Treaty, claims the benefit of U.S. Provisional Patent Application No. 63 / 327,998, having a filing date of April 6, 2022, and U.S. Provisional Patent Application No. 63 / 414,299, having a filing date of October 7, 2022, both of which are incorporated by reference herein for all purposes. [Background technology]
[0002]
[0002] Sulfur is a promising candidate for the next generation cathode in lithium battery systems, and lithium-sulfur (Li-S) batteries are one of the promising alternatives to current lithium-ion battery (LIB) technology due to their excellent specific energy density that can meet the emerging needs of advanced energy storage applications such as electric vehicles and grid-scale energy storage and delivery. However, achieving this high specific energy density is hindered by several challenges inherent to the nature of sulfur and its discharge products.
[0003]
[0003] One major challenge relates to the insulating properties of sulfur and its complete discharge product (Li2S), which often results in low availability of active materials and poor rate capability. The poor electronic conductivity of these species can be overcome by utilizing conductive hosts, but they are dilute and reduce the energy density, meaning that their mass ratio to the active material should be as low as possible.
[0004] Another challenge relates to the undesirable solubility of certain sulfur discharge products, so-called long-chain Li polysulfides (LiPS), in conventional ether-based liquid electrolytes. The solubility of long-chain LiPS promotes its free shuttle transport between the positive and negative electrodes, resulting in poor cyclability and capacity fade. Finally, sulfur goes through extensive expansion during discharge, resulting in mechanical degradation of the cathode over long sustained cycling operation. Despite efforts to engineer and control the undesirable LiPS shuttle effect and volume fluctuation induced degradation, progress has been mostly limited to low cycle numbers (100-200) or the need for complex and often expensive synthesis, which limits the rational development of new sulfur cathodes. Summary of the Invention [Problem to be solved by the invention]
[0005]
[0005] Currently, the majority of sulfur cathode research focuses on nanoarchitecture electrodes that use 2D and 3D host materials for sulfur, such as carbon nanotubes, graphene, conductive scaffolds, yolk-shell structures, and the like, to increase conductivity, mitigate LiPS shuttle, and accommodate volume fluctuations during discharge. Although these approaches have helped to increase the achievable capacity and sometimes cyclability, their synthesis methods are very complex, meaning that their production costs are high. Also, in operating cells, it is highly unlikely that these complex structures can be effectively reproduced after many charge-discharge cycles - meaning that capacity loss is essentially inevitable. Therefore, there remains a great need to develop novel, yet affordable and scalable cathode architectures that can enhance the rapid transport of Li ions to active sites for electrode reactions, accommodate discharge-induced volume expansion, and minimize the shuttle mechanism due to sulfur encapsulation. It is believed that a relatively simple and low-cost processing method to create electrodes that enable significantly improved cycle operation and life would be of great benefit to the art. [Means for solving the problem]
[0006]
[0006] Generally, the present disclosure is directed to a method for manufacturing a sulfur cathode, the method including the steps of dry mixing sulfur particles and a binder; adding a carbon source to the dry mixture; contacting the resulting dry mixture including the carbon source, sulfur particles, and binder with a solvent to form a cathode slurry; and removing the solvent from the cathode slurry to form a sulfur cathode, the sulfur cathode including a plurality of particles, each particle including a porous shell structure covering one or more of the sulfur particles.
[0007]
[0007] The present disclosure is also directed to an electrochemical cell comprising: a sulfur cathode comprising a plurality of particles, each particle comprising a porous shell structure covering one or more sulfur particles; an anode comprising lithium or a lithiated oxide material; and an electrolyte.
[0008]
[0008] These and other features, aspects, embodiments, and advantages of the present invention will become better understood with reference to the following description and appended claims.
[0009] A full and enabling disclosure of the present disclosure is set forth in more detail in the remainder of the specification, including reference to the attached drawings, in which: [Brief description of the drawings]
[0009] [Figure 1A]
[0010] FIG. 1A shows a scanning electron microscopy (SEM) image of a sulfur cathode that was process coated in the conventional manner - through a doctor blade. [Figure 1B]
[0011] FIG. 1B shows a scanning electron microscopy (SEM) image of a sulfur cathode that was process coated in the conventional manner - through a doctor blade. [Figure 1C]
[0012] FIG. 1C shows a scanning electron microscopy (SEM) image of a sulfur cathode process coated via conventional method-spraying. [Figure 1D]
[0013] FIG. 1D shows a scanning electron microscopy (SEM) image of a sulfur cathode process coated via conventional method-spraying. [Figure 1E]
[0014] FIG. 1E shows a scanning electron microscopy (SEM) image of a sulfur cathode process coated by the CBAD method-through a doctor blade. [Figure 1F]
[0015] FIG. 1F shows a scanning electron microscopy (SEM) image of a sulfur cathode process coated by CBAD method-through a doctor blade. [Figure 1G]
[0016] FIG. 1G shows a scanning electron microscopy (SEM) image of a sulfur cathode process coated via CBAD method-spraying. [Figure 1H]
[0017] FIG. 1H shows a scanning electron microscopy (SEM) image of a sulfur cathode process coated via CBAD method-spraying. [Diagram 2]
[0018] FIG. 2 shows the capacity retention of LSB cells prepared using various slurry preparation and coating methods. [Figure 3A]
[0019] FIG. 3A shows the galvanostatic charge-discharge profile of an LSB cell prepared by the conventional method-doctor blade. [Figure 3B]
[0020] FIG. 3B shows the galvanostatic charge-discharge profile of the LSB cell prepared by the conventional method-spraying. [Figure 3C]
[0021] FIG. 3C shows the galvanostatic charge-discharge profile of the LSB cell prepared by CBAD-doctor blade. [Figure 3D]
[0022] FIG. 3D shows the galvanostatic charge-discharge profile of the LSB cell prepared by CBAD-spraying. [Figure 4A]
[0023] FIG. 4A shows the long-term cycle life performance of the CBAD-spray electrode at C / 10. [Figure 4B]
[0024] FIG. 4B shows the rate capability of the CBAD-spray electrode at C / 10, C / 5, C / 2, and 1C. [Figure 5A]
[0025] FIG. 5A shows the coulombic efficiency of a sulfur cathode prepared by conventional method-doctor blading and cycled at C / 10 for 300 cycles. [Figure 5B]
[0026] FIG. 5B shows the coulombic efficiency of a sulfur cathode prepared by conventional method-spraying and cycled at C / 10 for 300 cycles. [Figure 5C]
[0027] FIG. 5C shows the coulombic efficiency of a sulfur cathode prepared by the CBAD method-doctor blade and cycled at C / 10 for 300 cycles. [Figure 5D]
[0028] FIG. 5D shows the coulombic efficiency of the sulfur cathode prepared by CBAD method-spraying and cycled at C / 10 for 300 cycles. [Figure 6A]
[0029] FIG. 6A shows an SEM image of the CM-W-1 based electrode. [Figure 6B]
[0030] FIG. 6B shows an SEM image of the PA-W-1 based electrode. [Figure 6C]
[0031] FIG. 6C shows an SEM image of a PV-W-1 based electrode. [Figure 6D]
[0032] FIG. 6D shows an SEM image of a CMC-based electrode. [Figure 6E]
[0033] FIG. 6E shows an SEM image of the PAA-based electrode. [Figure 6F]
[0034] FIG. 6F shows an SEM image of a PVP-based electrode. [Figure 7A]
[0035] FIG. 7A shows an SEM image of the pristine NMP CM-W-1 based electrode. [Figure 7B]
[0036] FIG. 7B shows an SEM image of the PA-W-1 based electrode with pristine NMP. [Figure 7C]
[0037] FIG. 7C shows an SEM image of the PV-W-1 based electrode with pristine NMP. [Figure 7D]
[0038] FIG. 7D shows an SEM image of a pristine NMP CMC-based electrode. [Figure 7E]
[0039] FIG. 7E shows an SEM image of the PAA-based electrode with pristine NMP. [Figure 7F]
[0040] FIG. 7F shows an SEM image of the PVP-based electrode with pristine NMP. [Figure 8A]
[0041] FIG. 8A shows the capacity retention of PAA, PVP, and CMC-based electrodes in an NMP-based system. [Figure 8B]
[0042] FIG. 8B shows the capacity retention of PAA, PVP, and CMC-based electrodes in a water-based system. [Figure 8C]
[0043] FIG. 8C shows the voltage profile of CMC with water and NMP-based cathodes during the second cycle. [Figure 8D]
[0044] FIG. 8D shows the voltage profile of PAA with water and NMP-based cathodes on the second cycle. [Figure 8E]
[0045] FIG. 8E shows the voltage profile of PVP with water and NMP based cathodes during the second cycle. [Figure 9A]
[0046] FIG. 9A shows an SEM image of a precycled electrode with CM-N-2. [Figure 9B]
[0047] FIG. 9B shows an SEM image of a precycled electrode with PA-N-2. [Figure 9C]
[0048] FIG. 9C shows an SEM image of a precycled electrode with PV-N-2. [Figure 9D]
[0049] FIG. 9D shows the capacity retention plot of the Li—S cell. [Figure 10A]
[0050] FIG. 10A shows an SEM image of a precycled electrode with CM-N-3. [Figure 10B]
[0051] FIG. 10B shows an SEM image of a precycled electrode with PA-N-3. [Figure 10C]
[0052] FIG. 10C shows an SEM image of the precycled electrode with PV-N-3. [Figure 11A]
[0053] FIG. 11A shows a post-mortem SEM image of a precycled cell with a shell covering the PV-N-1 particles. [Figure 11B]
[0054] FIG. 11B shows a post-mortem SEM image of the electrode surface after 20 charge-discharge cycles with a shell covering the PV-N-1 particles. [Figure 11C]
[0055] FIG. 11C shows a post-mortem SEM image after rinsing the cycled cell with a shell covering the PV-N-1 particles. [Figure 11D]
[0056] FIG. 11D shows a post-mortem SEM image of a precycled cell without a shell covering the PV-N-3 particles. [Figure 11E]
[0057] FIG. 11E shows a post-mortem SEM image of the electrode surface after 20 charge-discharge cycles without a shell covering the PV-N-3 particles. [Figure 11F]
[0058] FIG. 11F shows a post-mortem SEM image after rinsing the cycled cell with no shell covering the PV-N-3 particles. [Figure 12]
[0059] FIG. 12 shows the particle structure change caused by the charge / discharge process. [Figure 13]
[0060] FIG. 13 shows a process for forming a sulfur cathode based on a conventional method compared to the “controlled binder-dissolution after dry-mixing (CBAD)” method. [Figure 14]
[0061] FIG. 14 shows an electrochemical cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010]
[0062] Repeat use of reference characters in the present specification and drawings is intended to represent same or analogous features or elements of the present disclosure.
[0063] Reference will now be made in detail to the exemplary embodiments of the present disclosure. Those skilled in the art will understand that this disclosure is merely a description of exemplary embodiments, and is not intended to limit the broader scope of the present disclosure.
[0011]
[0064] In general, the present disclosure is directed to a simple and scalable method of producing a sulfur cathode. For example, the method includes dry mixing sulfur particles and a binder; adding a carbon source to the dry mixture; and contacting the dry mixture with a solvent to form a cathode slurry. In one embodiment, the sulfur cathode includes a plurality of particles, each particle including a porous shell structure that covers one or more of the sulfur particles. The porous shell structure may include carbon from the carbon source and at least a portion of the binder. The solubility of the binder in the solvent is limited to control the diffusion of the solvent into the polymer chains of the binder. The solubility can be set by several variables including the solvent to binder ratio, temperature, time, degree of stirring / mixing, the presence of surfactants or other dissolved species, and the presence of secondary solid additives. From this process, a solid swollen network of the binder that adheres to the sulfur and carbon particles can be achieved. The swollen network may provide a buffer for volume expansion during discharge and may prevent dissolution of discharge products (e.g., soluble polysulfides) in the electrolyte by physical entrapment. Embodiments may provide high electrode cycling potential.
[0012]
[0065] According to the present disclosure, the binder may be a polymeric binder. The binder polymer may include electrode binders as generally known in the art, examples of which may include, but are not limited to, polytetrafluoroethylene (PTFE), carboxymethylcellulose (CMC), rubbers such as styrene butadiene rubber (SBR) and natural latex rubber, polyacrylic acid (PAA), such as lithium polyacrylate (LiPAA), polyurethane, ethylene vinyl acetate, polyacrylamide, starch, polyvinylidene fluoride, acrylonitrile copolymer, polyacrylonitrile, poly(vinylidene fluoride)-hexafluoropropene, or combinations thereof. The binder may be a polymer that is covalently bonded to one or more components of the electrode after formation of the electrode.
[0013]
[0066] In the conventional electrode processing method, the binder (e.g., PVDF) is dissolved in NMP solvent to obtain a viscous binder solution. The active material and conductive host, such as sulfur and Vulcan™ (carbon) powder, are mixed in a dry state and then combined with a liquid to form a slurry or dispersion. The pre-dissolved binder is then added to the active material / carbon wet dispersion, mixed, coated onto the current collector, and dried. The result is a dense and continuous carbon / binder medium that holds the sulfur particles in place and in contact with the conductive carbon and current collector. This slurry preparation and electrode processing method worked well for lithium-ion battery (LIB) electrodes, but in the case of sulfur cathodes, this compact structure leads to mechanical degradation of the electrode due to insufficient exposure of the sulfur active material to the electrolyte and volumetric fluctuations of sulfur during charging and discharging. As a result, conventionally fabricated sulfur cathodes suffer from poor performance and life span. Therefore, a new “outside the LIB box”, affordable, and scalable electrode design and fabrication approach is needed to tailor it to lithium-sulfur batteries (LSB).
[0014]
[0067] Herein, an affordable and scalable electrode processing method known as "controlled binder-dissolution after dry mixing (CBAD)" has been developed that can produce highly durable sulfur cathodes using electrode components readily known in the art. In an embodiment, the sulfur cathode may include a sulfur-containing source. For example, the sulfur-containing source may include sulfur particles in the form of, but not limited to, a powder. In an embodiment, the sulfur particles can be present in the cathode in an amount of about 50% to about 95% by weight, such as about 55% to about 75% by weight, such as about 60% to about 70% by weight, or any range therebetween. For example, the sulfur particles may be present in the cathode at a concentration of 70% by weight.
[0015]
[0068] In one embodiment, the sulfur can be pre-processed to prepare small size particles and deagglomerate them prior to fabrication of the electrode. The sulfur particles can range in size from about 1 μm to about 40 μm, such as from about 5 μm to about 35 μm, such as from about 10 μm to about 25 μm, or any range therebetween.
[0016]
[0069] The sulfur cathode may include a binder. For example, the binder may include, but is not limited to, polyvinylidene fluoride, styrene butadiene rubber, carboxymethyl cellulose, acrylonitrile copolymer, polyacrylic acid, polyacrylonitrile, poly(vinylidene fluoride)-hexafluoropropene, or combinations thereof. The binder may be present in the cathode in an amount of about 1% to about 15% by weight, such as about 2.5% to about 12.5% by weight, such as about 5% to about 10% by weight, or any range therebetween.
[0017]
[0070] The sulfur cathode may also include conductive particles. In one embodiment, the sulfur cathode may include carbon particles. The carbon particles may include carbon black, activated carbon, carbon fiber, graphitized carbon, or mesoporous carbon. The utilization of sulfur may also be increased by increasing electronic conductivity through the utilization of carbon with higher surface area, such as Ketjenblack® and sulfur-carbon composites. Generally, the electrically active particles are present in the cathode at a concentration of about 1% to about 25% by weight, such as about 5% to about 22% by weight, such as about 10% to about 20% by weight, such as about 12.5% to about 15% by weight, or any range therebetween.
[0018]
[0071] In one embodiment, the sulfur cathode disclosed herein may include sulfur powder (Sigma-Aldrich, part #414980), carbon black (Vulcan™ XR-72), and polyvinylidene fluoride (PVDF) binder. In one embodiment, the ratio of sulfur to carbon to binder is about 70:20:10.
[0019]
[0072] To form the electrode, the process of the present disclosure allows the sulfur 102 (FIG. 13) and binder 104 to first be ground individually in a pestle and mortar. The carbon 100 can be used as received, depending on the particle size. The sulfur 102 and binder 104 are then mixed together in a dry state and sonicated to ensure a homogenous mixture. Dry carbon 100 can then be added to the mixture of sulfur 102 and binder 104. The dry mixture of sulfur, carbon, and binder can then be sonicated and then stirred using a clean, dry magnetic stir bar. After the dry mixture is formed, the solvent 106 is added to the dry mixture and stirred to form the cathode slurry. In one embodiment, the solvent 106 to binder 104 ratio is about 50 μL / mg. (結合剤) to about 300 μL / mg (結合剤) For example, about 100 μL / mg (結合剤) to about 200 μL / mg (結合剤)or any range therebetween (FIG. 13). Through control of the duration of stirring and rocking, the kinetics of binder 104 dissolution can be controlled and held in a swollen state - an intermediate dissolution state for the polymer that is between the pure polymer state and the pure solvent state. The resulting CBAD electrode may include a sponge-shaped porous shell 112 of swollen binder surrounding the sulfur 102 and carbon 100 particles (FIG. 13).
[0020]
[0073] Without being bound to any particular theory, it is understood that by initially mixing the binder and sulfur powder in the absence of carbon, the sulfur particles can mix with the solvent and later swell to form a porous shell 112 containment around the sulfur particles (102) in the porous binder medium 110. This porous shell allows for better exposure of the sulfur particles to the electrolyte and can accommodate sulfur volume expansion during discharge. These improvements can result in higher electrode durability. In general, the porous shell 112 structure can define a thickness that is about 1 μm to about 5 μm, such as about 1.5 μm to about 4.5 μm, such as about 2 μm to about 3.5 μm, or any range therebetween. Conversely, conventional sulfur cathode processing methods form a dense and continuous binder medium that holds the sulfur particles tightly and does not provide enough space for sulfur volume expansion during discharge (FIG. 13).
[0021]
[0074] Thus, the cyclability of Li-S batteries incorporating electrodes formed as described herein can be improved through control of the level of binder dissolution in processing solvents. The result is longer battery life, enabling the penetration of these cells into new applications.
[0022]
[0075] The low-cost and scalable processing method disclosed herein can be used to form highly durable cathodes containing sulfur, electroactive particles, and polymer binder. The method is based on the preparation of sulfur cathode slurry via a simple approach using conventional electrode ingredients. During the formation process, the solubility of the binder in the solvent is limited by controlling the diffusion of the solvent into the entangled polymer chains through various solvent:binder ratios, diffusion times, and stirring. In one embodiment, the diffusion time is about 20 hours to about 30 hours, such as about 22 hours to about 27 hours, or any range therebetween. In another embodiment, the stirring time may be about 300 RPM to about 1000 RPM, such as about 450 RPM to about 750 RPM, or any range therebetween.
[0023]
[0076] During the formation of the cathode, the method used to coat the swollen binder material can also be used to provide further improvements to the cathode. In some embodiments, spraying can be used to form a highly porous swollen binder network. In some embodiments, the sprayed material (commonly referred to as the electrode ink) can be aerated. Alternatively, the use of traditional doctor blade techniques can result in a denser cathode while still providing improvements through the swollen binder of the cathode.
[0024]
[0077] In one embodiment, the sulfur cathode disclosed herein may be coated onto the current collector using standard coating techniques known in the art. For example, the coating technique may be spray coating, which involves the layer-by-layer dispersion and deposition of a well-mixed electrode ink onto the current collector. The spraying may be done using an airbrush. As the electrode, enough material is generally placed on the current collector to cover it entirely. The layer is then allowed to dry (e.g., at 100° C.) before another layer of ink is sprayed and dried. The process can be repeated until the desired loading is reached. Finally, the electrode can be kept under vacuum for 48 hours to ensure that all the solvent has been removed.
[0025]
[0078] In one embodiment, the coating method may include a doctor blade technique. In this embodiment, the current collector substrate may be placed on a vacuum table in an enclosure that holds it in place. A homogeneous, well-mixed ink may be placed on the current collector. The blade may then be moved slowly along the substrate, spreading the ink onto the current collector to form a uniform thin layer. The electrode may then be allowed to dry, for example at room temperature. Doctor blade electrodes may have a longer drying time than spray-coated electrodes, since the layer may be dense and the drying does not need to be heat-assisted. Furthermore, it is worth noting here that when spray-coated electrodes are formed, only a small amount of ink is used at each step, and drying occurs almost instantly due to the low total volume of heat and solvent per step. This means that the electrode is never actually in a highly liquid state (excess solvent) during its formation. During doctor blade deposition, all of the ink is spread onto the current collector at once, and drying occurs from a highly liquid state.
[0026]
[0079] Regardless of the coating method utilized, the cycling performance of sulfur cathodes prepared via the disclosed method can exhibit an impressive capacity retention of 74% after 1000 cycles, suggesting a significant improvement in shuttle effect and active material preservation. The disclosed production process can be adapted for battery manufacturing and for scale-up of the disclosed cells.
[0027]
[0080] Through controlled dissolution of the binder after dry mixing of the electrode components, a porous medium of the binder can be formed that provides a larger surface area and therefore proper adhesion while facilitating high redox reactions. Through this method, called CBAD, which combines spray coating techniques, a protective cover shell structure can be formed around the sulfur particles that prevents polysulfide dissolution by physical entrapment. The shell structure also accommodates the volume expansion of sulfur during discharge and subsequently prevents mechanical degradation in the sulfur electrode. These structural features result in a high capacity and highly durable sulfur cathode. This finding helps establish a low-cost and scalable manufacturing process for stable and highly durable sulfur cathodes for LSB.
[0028]
[0081] In one embodiment, the cathode formed according to the CBAD method disclosed herein may be incorporated into an electrochemical cell 116 (FIG. 14). The electrochemical cell 116 may include a sulfur cathode, an anode, and a liquid electrolyte. In one embodiment, the sulfur cathode may include a porous shell 112 in contact with a porous medium. For example, the sulfur cathode may be formed from a porous medium such as, but not limited to, elemental sulfur (S8), Li2S x or combinations thereof. The general formula is Li2S x where x is equal to or greater than 4. For example, the cathode active material may be Li2S4, Li2S5, Li2S6, Li2S7, or Li2S8.
[0029]
[0082] The electrochemical cell may also include an anode. The anode may include a porous anode active material and an anode current collector. Generally, metallic lithium or a lithium alloy may be used as the anode active material to take advantage of the high energy density of lithium metal. According to one embodiment, the anode may include silicon, lithium, or a lithiated oxide material. For example, the lithiated oxide may be Li x Z y O awhere Z represents a non-metallic element, and x, y, and a are each greater than or equal to 1. In one embodiment, the lithiated oxide includes, but is not limited to, lithiated silicon, lithiated silicon oxide, or a combination thereof.
[0030]
[0083] In one embodiment, the electrochemical cell may include an electrolyte 116, such as lithium ion conducting particles. For example, the electrolyte may include, but is not limited to, lithium bis(trifluoromethane)sulfonimide (LiTFSI), lithium hexafluorophosphate (LiPF6), or combinations thereof. The electrodes may separate the sulfur cathode and the anode.
[0031]
[0084] In one embodiment, the electrochemical cell may further include a current collector. For example, the current collector may include, but is not limited to, aluminum.
[0085] In another embodiment, the cathode active material may be a metal oxide intercalation cathode active material known in the art. The cathode may include a metal oxide compound along with other components, such as graphite, and an electrolyte / binder that may provide ion transport or may include only a metal oxide intercalation material, as desired.
[0032]
[0086] Metal oxide cathode active materials can be prepared having a unit structure characterized by the ability to insert lithium ions in an electrochemical reaction. Such compounds are called intercalation compounds and include transition metal oxides that have reversible lithium insertion capability. The transition metals of the cathode active materials may include one or more of V, Co, Mn, Fe, and Ni.
[0033]
[0087] Electrochemical cells can provide high energy density, high cycle operating speed (high power capability), and safe battery technology. Electrochemical cells can be used to form lightweight metal-supported solid-state lithium-ion batteries that can meet the existing challenges in battery technology. Furthermore, electrochemical cells can find immediate applications in electric vehicles, aerospace applications, and renewable and grid energy storage, among others.
[0034]
[0088] The battery may include one or more cells sealed in a case according to standard practice, for example the battery may be a lithium-sulfur battery.
[0089] Additionally, certain aspects of the present disclosure may be better understood by the following examples, which are intended to be non-limiting and illustrative in nature, and it will be further understood that the compositions described in the examples may be substantially free of any material not expressly described. EXAMPLES
[0035]
[0090] To investigate the effect of preparation methods on the structure and electrochemical performance of sulfur cathodes, the slurries produced by both conventional and disclosed CBAD methods were coated onto aluminum (Al) foil as current collector. Considering the additional impact of the coating process on the electrode structure, two coating techniques, doctor blade and spraying, were investigated for each slurry. After coating, all four electrodes were vacuum dried at room temperature for 48 h. The results of structural characterization and electrochemical evaluation for these electrodes are presented in Figure 1.
[0036]
[0091] Agglomerated sulfur structures were observed on all four electrodes. Nevertheless, the doctor blade coating process resulted in a broader particle size distribution (average size 33.2-33.3 μm) and larger sized aggregates (Figures 1A and 1E), whereas the spraying method (Figures 1C and 1G) notably formed a more uniform structure and homogenous particle size distribution. This is attributed to the spray-induced atomization of the slurry, which provides a more uniform coating layer with finer aggregates.
[0037]
[0092] Further, a porous binder medium was observed in all four electrodes. However, the sprayed electrodes showed a less dense and more spongy form of porous medium (FIGS. 1D and 1H) when compared to those treated with doctor blade (FIGS. 1B and 1F). Interestingly, when the spray-coating and CBAD methods were combined, a notable difference was observed in the microstructure of the electrodes, as shown in FIG. 1H, with a fine shell-like structure encasing the sulfur particles. However, the shell cover, although present, was very faint in the CBAD electrodes prepared by the doctor blade method (FIG. 1F), and was absent when the conventional slurry preparation approach was employed, regardless of the coating method (FIGS. 1B and 1D). These observations suggest that it is the combination of the CBAD method and spray-coating that results in the desired porous shell structure around the sulfur particles.
[0038]
[0093] The pre-cycling structures of the spray and doctor blade coated CBAD and conventional electrodes were characterized using a high resolution field emission scanning electron microscope (FE-SEM), a Zeiss™ Gemini 500 FE-SEM. Microscopy may be performed at a working distance of about 8 mm to about 12 mm, using an accelerating voltage of 15 kV for the electron beam and a highly efficient secondary electron detector.
[0039]
[0094] The spray and doctor blade coated CBAD and conventional electrodes were then assembled into coin cells. In detail, each electrode was punched into a 16 mm diameter disk using a precision disk cutter (MTI Corp.) and then used as the cathode in the coin cell. In a typical procedure, a 16 mm diameter Li metal foil (99.9%, Alfa Aesar) as the anode was placed in the center of the coin cell base, and then 10 uL / mg LiFSI (Sigma-Aldrich, USA) salt was added to the base in a commonly used ether-based solvent mixture: 1:1 volume ratio of dimethoxyethane (DME, 99%, Sigma-Aldrich) and dioxolane (DIOX, 99%, Sigma-Aldrich) consisting of 1 M LiTFSI (Sigma-Aldrich, USA) salt and 2 wt% LiNO3 (99%, Alfa Aesar) as an additive. (カソード中の活性材料) of electrolyte was dispensed evenly onto the Li foil. A separator (Celgard® 2320 trilayer polymer (diameter: 19 mm)) was then placed on top and centered, followed by an additional 10 uL / mg (カソード中の活性材料) A dose of electrolyte was added. A gasket was then placed along the perimeter of the coin cell base to ensure proper sealing of the coin cell. A sulfur cathode disk was then placed on top and centered on the top of the Li / electrolyte / separator / electrolyte stack, with the electrode material facing the separator. A spacer disk and spring were also used to evenly distribute pressure and electrical continuity. Finally, the coin cell cap was placed on top and the coin cell was sealed using an MTI hydraulic press (MSK-110) at 5.2 MPa (750 psi) pressure. The coin cells were assembled inside an argon-filled (ultra-high purity 5.0 argon, Airgas®) MBRAUN LABmaster SP glove box with oxygen and humidity content of <0.1 ppm.
[0040]
[0095] After cell assembly, all four electrodes (conventional doctor blade coated, conventional spray coated, CBAD doctor blade coated, and CBAD spray coated) were tested for their cycling performance using an Arbin battery cycler (Version 3.0 Build 7.29). The cells were not aged or conditioned before cycling tests. The cycling performance of the cells was investigated through constant current (CC) cycling from 1.8V to 2.8V at 0.1C. The long-term cycling of the best performing cell was studied up to 1000 cycles. The C-rate capability of the best performing cell was evaluated at 0.1C, 0.2C, 0.5C, and 1C rates and back to 0.1C for 10 cycles each.
[0041]
[0096] The cells were tested for their cycling performance at C / 10 for 200 cycles. The cells were allowed to equilibrate at C / 10 for several cycles. Their discharge performance for the following 200 cycles after equilibration at C / 10 is shown in FIG. 2, and the discharge capacity of the cells is considered to be highly influenced by the electrode preparation method. As shown, the cells made from the spray coating method had significantly higher discharge capacity compared to their counterparts made from the doctor blade method. This spray coating method resulted in smaller and more uniform active particles. However, the smaller particles have better exposure and facilitate improved conversion reaction as opposed to the larger aggregates produced by the doctor blade technique. The large aggregate size in the doctor blade electrode leaves most of the particles unreacted, resulting in low capacity. However, the electrodes made from the CBAD method in each group provided stable discharge capacity.
[0042]
[0097] In conventional electrodes, capacity degradation occurred after a few cycles. The major pathway through which capacity is reduced for Li-S batteries is through lithium polysulfide (LiPS) shuttling. The discharge behavior observed here is understood by studying the evolution of the voltage profile over a few cycles.
[0043]
[0098] The charge-discharge profiles of the four sulfur electrodes within the voltage window of 1.8 V to 2.8 V were observed at 50, 100, and 150 cycles and are shown in Figure 3. As observed, the voltage profile of the electrodes combines two distinct plateaus, indicating the formation of higher order lithium polysulfides at the higher voltage and the formation of short chain polysulfides at the lower voltage. The plateau at the higher voltage plateau represents the formation of soluble LiPS, while the lower voltage plateau indicates the further reduction of LiPS to insoluble Li2S2 / Li2S products. The loss of LiPS can be quantified by the ratio of the capacities of these two plateaus. The reduction at the higher voltage indicates the loss of polysulfides.
[0044]
[0099] As can be observed, regardless of the coating technique used, there was a reduction in the length of the higher voltage plateau in the conventional electrodes (Figures 3A and 3B) between 50 and 150 cycles. This indicates a loss of LiPS that was likely involved in subsequent cycling, which manifests in the observed capacity fading. Notably, this phenomenon was not observed in the CBAD electrodes, where the plateau length remained similar throughout, indicating that soluble long-chain polysulfides were not permanently lost during cycling. The CBAD electrodes therefore produced stable capacity throughout the entire 200 cycles that the electrodes were tested for.
[0045]
[0100] Several binder compositions were investigated. PVDF does not have polysulfide anchoring ability. Therefore, the polysulfide containment ability of the particular electrode may be attributed to a novel electrode processing technique that resulted in a shell around the sulfur particles. As a result, the escape of soluble polysulfides can be significantly reduced by trapping them in the porous shell and by the long transport length provided by the shell for conversion in subsequent cycles.
[0046]
[0101] Due to the excellent initial cycle operation behavior of the CBAD-sprayed electrode, this electrode was tested for its long cycle life up to 1000 cycles (FIG. 4A). In one embodiment, the electrode disclosed herein can retain more than 70% of the capacity after about 1000 charge-discharge cycles relative to the initial charge-discharge cycle. An initial capacity of 451 mAh / g was observed on the first cycle of one exemplary electrode. The capacity surprisingly increased to its highest value of 543 mAh / g at about 300 cycles. Up to 700 cycles, the CBAD-sprayed cathode provided an average capacity of 500 mAh / g with a retention percentage of 90%. The final capacity of this electrode at 1000 cycles was 400 mAh / g, providing a remarkable capacity retention of 74%. It is noteworthy that, so far, this value is the highest achievable capacity and cyclability for Li-S batteries produced through a simple and scalable processing technique using commercially available cost-effective materials.
[0047]
[0102] The rate capacity of the CBAD-sprayed electrode was also evaluated by cycling the cell at various C-rates, as shown in FIG. 4B. At C / 10, the cell maintains a capacity of about 550 mAh / g, decreasing to about 310 mAh / g at 1C. Lower capacities are expected at higher current rates. However, the cell regains nearly all of its capacity when returned to a lower C-rate, suggesting reasonable kinetics and charge-discharge transfer in this electrode. The discharge capacity achieved with this method was lower than the theoretical capacity, likely due to the inability to reach all parts of the sulfur particles, as large agglomerates may cause low utilization of the active material.
[0048] Example 1
[0103] Various sulfur cathodes were fabricated with the same components (70% sulfur, 20% conductive carbon, and 10% binder). All components were mixed in dry form but with different solvent systems (Table 1). For all cathodes in classes 1 and 2, the powdered components were mixed and stirred in the solvent for 24 hours. For class 3, the components were mixed for one week. In all electrodes, the required amount of solvent to form a sprayable viscosity is used. Due to different solubility trends of the solvents, the amount of water and NMP used varied slightly but was consistent within the same class, respectively.
[0049]
[0104] Galvanostatic charge-discharge tests were performed on an Arbin® battery tester at room temperature with a voltage range of 1.8 V to 2.8 V at C / 10 current density. The nomenclature of each cell in Table 1 follows the pattern BSx, where B represents the binder used (CM for CMC, PV for PVP, and PA for PAA); S = solvent used (N for NMP, and W for Water); x = electrode class indicating stirring time (1 = ink stirred for 1 day). For example, a CMC-based electrode in water with 5 μL / mg electrode material stirred for 24 hours is designated as CM-W-1.
[0050] [Table 1]
[0051]
[0105] Morphological examination was performed using scanning electron microscopy (SEM) to investigate the effect of the binder dissolution environment on the physical microstructure of the electrode. Figures 6A-6F show SEM images of the electrodes in water and NMP solvents, respectively. As observed, the cathode structure is composed of fine particles distributed throughout the electrode matrix. In the electrode treated with NMP (Figure 8), the particles appear to be more finely dispersed on the current collector. Due to the hydrophobic nature of the sulfur and carbon particles, they are less dispersible and therefore cause individual sulfur particles to be isolated in the aqueous dissolving binder.
[0052]
[0106] Notable differences were observed between the morphology of the two classes of electrodes. For example, the shell-like structures encapsulating individual sulfur particles in the NMP-treated electrodes are independent of the binder used, whereas such shell covering is not observed in the aqueous systems. Looking deeper into the structures with high magnification SEM imaging, it is seen that the size of the shells around the particles varies; the PAA-based electrodes possess a thin shell, whereas the shells in both the PVP- and CMC-based electrodes are larger and more visible. The shell thickness covers a range between 1 μm and 5 μm.
[0053]
[0107] The ink viscosity in all electrodes fabricated is similar. This significant difference in the morphology of the electrodes may be due to chemical interactions between the solvent and the binder, independent of the binder used. PAA, PVP, and Na-CMC have oxygen atoms attached to the carbon skeleton that are hydrogen bond acceptors that increase their solubility in water. As a result, the electrodes treated with water are dense with particles close to each other. However, NMP is an aprotic solvent that does not form hydrogen bonds and is believed not to penetrate the binder, resulting in swelling and dissolving the binder to form a shell around the particles after drying.
[0054] Example 2
[0108] To investigate the effect of the electrode preparation process on the electrochemical performance of the sulfur cathode, galvanostatic charge-discharge cycling was performed at 0.1 C rate (C) between 1.8 and 2.8 V at room temperature. The long-term cycling performance is compared in Figures 8A and 8B. In all cells, an initial irreversible capacity loss is observed, which is due to the reduction of sulfur forming the solid electrolyte interface. In the NMP system, the initial capacity of the cells is similar, about 614 mAh / gS. After 1000 cycles, the specific discharge capacity of the PV-N-1 cathode stabilizes at about 500 mAh / gS, which is higher than that of the CM-N-1 and PA-N-1 sulfur cathodes. By comparison, a similar experiment performed on an aqueous-based cathode with the same electrode components and composition as shown in Figure 8B but with water as the solvent shows a very low discharge performance under the same test conditions. Among all cells prepared in an aqueous system, the PV-W-1 cathode shows a higher discharge capacity, but still lower than that of the PV-N-1. In general, all aqueous processed cathodes showed lower discharge capacity than their NMP-based counterparts. Moreover, capacity fading after extended cycling is less intense in NMP-based electrodes. This combined improved electrochemical performance is attributed to the unique structure of the electrodes, which exhibits a shell covering the active particles, with higher discharge capacity and lower capacity fading rates. In a sense, the shell ensures better accessibility to the higher sulfur surface for reactions resulting in better utilization of sulfur. It also provides a buffer against volume expansion over extended cycling, and with it, better diffusion paths for lithium ions.
[0055]
[0109] As shown in Figures 3C-3E, the voltage difference (ΔV) between the charge-discharge plateaus in the second cycle is larger for the aqueous treated cathode, which is caused by the hydrophobicity of the active electrode components. This hydrophobicity, which causes poor dispersion, results in high polarization. The effect of poor dispersion and high polarization is also observed in the Coulombic efficiency as shown in Figure 5. In general, the Coulombic efficiency of the aqueous electrodes is lower than that in the NMP-based electrodes, justifying the compatibility of the electrode components with the solvent in the method adopted for the electrode fabrication.
[0056]
[0110] The lower capacity fading rate observed in the NMP-based cells can also be justified for the shell-like morphology of the electrodes. Most of the capacity fading in Li-S batteries is mainly through the transition of soluble lithium polysulfides into the electrolyte. The shell cover, among other functions, also functions to accommodate the polysulfides by providing physical confinement against diffusion into the electrolyte. Thus, redox reactions can take place within the shell space containing the polysulfides. The effectiveness of the shell cover in confining the LPS is indicated by the nearly constant ratio of the high potential plateau to the lower plateau (QH / QL) through various cycle numbers. A reduced ratio indicates LPS loss. The ratio of QH to QL shown in Table 2 for 50, 100, and 500 cycles of all cells indicates that the presence of the shell in the NMP-based cells is crucial in preventing the loss of LPS, which leads to better capacity retention. Therefore, this high electrochemical performance can be attributed to better lithium ion diffusion, lithium polysulfide confinement, and robust mechanical properties of the electrode through the formation of an intrinsic shell around the particles.
[0057] [Table 2]
[0058]
[0111] The kinetics of the shell covering, and the subsequent electrochemical performance of the cells, are further elucidated by increasing the volume of the solvent as well as the stirring time. First, an excess volume of NMP solvent was added to the electrode material and stirred for 24 hours. The resulting SEM images and capacity retention of CM-N-2, PA-N-2, and PV-N-2 are presented in Figure 4. The SEM images show that the shell covering completely disappears in PA-N-2, while it also shrinks in CM-N-2 and PV-N-2 cathodes. This indicates that the increase in the volume of the solvent creates a dilute environment around the sulfur particles, reducing their tendency to form a robust shell when dried. This variation in shell appearance results from the different solubility of the polymer in the solvent. As a result, the morphology of the electrode is affected. This effect is revealed in the capacity retention plot shown in Figure 4B. The discharge capacity of the cells is much lower than that obtained in Figure 3B for the same cathode components, which further highlights the significance of the shell covering in enhancing the physical properties of the cells.
[0059] Example 3
[0112] To further understand the dissolution kinetics of the binder in the solvent, extended stirring times with excess amount of solvent are used. From the morphological examination through SEM shown in Figures 10A-10C, the shell cover that initially encapsulated the active sulfur particles has now completely disappeared. This phenomenon is indicated by the polarity-induced interactions among the NMP molecules, which results in the antiparallel configuration of the NMP rings when the population of NMP molecules increases.
[0060]
[0113] Galvanostatic cycling shows an initial high discharge capacity that gradually fades as cycling proceeds. Both the discharge capacity and capacity retention per cathode are significantly lower than the reference cell in Figure 7B, again demonstrating the positive impact of the shell cover on morphology and electrochemical performance.
[0061]
[0114] A post-mortem SEM analysis of the structure of the top surface of the cathode surface after 20 galvanostatic cycling of PV-N-1 was performed as shown in FIG. 11 to show the effect of the shell during cycling. After 20 cycles of the charge-discharge process, the fully lithiated state of PV-N-1 still possesses an intact structure consisting of sulfur particles uniformly distributed on the current collector. The particles also appear larger, indicating expanded particles due to the discharge process that led to the formation of Li2S products. Treatment of the electrode with dimethoxyethane (DME) to dissolve the species on the surface leaves holes, indicated by the white dashed ovals, of the same shape as the shell cover encapsulating the particles. Conversely, the surface of PV-N-3 is covered by large deposits of discharge products, indicating that the dissolved polysulfides are not trapped within the cathode structure. This deposition of discharge products on the electrode surface is one of the reasons for the low capacity, which is due to the surface cover limiting the accessibility of the active sulfur surface, as well as capacity fading due to wasting polysulfides. Several other approaches have been developed to ensure better electrochemical deposition and diffusion of lithium polysulfides, including creating a physical barrier through separator design, creating interlayer protection on the surface of the cathode and also on the surface of the anode to prevent polysulfides from reacting with lithium metal, and creating a physical barrier by encapsulating sulfur particles in carbon nanospheres and nanotubes. Protection of the electrode integrity has also been shown to affect cathode performance by protecting the particles from mechanical damage. The shell covering the sulfur particles appears to perform a dual function, creating a mechanical buffer against particle fracture as well as a physical trap for lithium polysulfides, as shown in Figures 11A-11B.
[0062]
[0115] These and other modifications and variations to the present invention may be practiced by those of ordinary skill in the art without departing from the spirit and scope of the present invention as more particularly set forth in the appended claims. Moreover, it should be understood that aspects of the various embodiments may be interchangeable both in whole or in part. Moreover, those skilled in the art will appreciate that the foregoing description is merely illustrative and does not limit the invention as further so described in such appended claims.
Claims
1. 1. A method for producing a sulfur cathode, comprising: dry mixing the sulfur particles and the binder; adding a carbon source to the dry mixture; and contacting the resulting dry mixture, including the carbon source, the sulfur particles, and the binder, with a solvent to form a cathode slurry; and removing the solvent from the cathode slurry to form the sulfur cathode. wherein the sulfur cathode comprises a plurality of particles, each particle comprising a porous shell structure covering one or more of the sulfur particles; method.
2. The method of claim 1 , wherein the porous shell structure comprises carbon from the carbon source and at least a portion of the binder.
3. The method of claim 1 , wherein the porous shell structure defines a thickness that is from about 1 μm to about 5 μm.
4. The method of claim 1 , wherein the sulfur particles comprise sulfur powder.
5. The method of claim 1 , wherein the dry mixture comprises the sulfur particles in an amount of about 55% to about 95% by weight.
6. The method of claim 1 , wherein the dry mix comprises the binder in an amount of about 1% to about 15% by weight.
7. The method of claim 1 , wherein the binder comprises a polymeric binder.
8. 8. The method of claim 7, wherein the polymeric binder comprises a polymer selected from the group consisting of polyvinylidene fluoride, styrene butadiene rubber, carboxymethyl cellulose, acrylonitrile copolymers, polyacrylic acid, polyacrylonitrile, poly(vinylidene fluoride)-hexafluoropropene, and combinations thereof.
9. 10. The method of claim 1, wherein the carbon source comprises carbon black, activated carbon, carbon fiber, graphitized carbon, or mesoporous carbon.
10. The method of claim 1, wherein the solvent comprises n-methyl-2-pyrrolidone, dimethoxyethane, dioxolane, water, or a combination thereof.
11. The cathode slurry is about 50 μL / mg (結合剤) to about 300 μL / mg (結合剤) The method of claim 10, comprising the solvent in a concentration of
12. 1. An electrochemical cell comprising: a sulfur cathode comprising a plurality of particles, each particle comprising a porous shell structure covering one or more sulfur particles, the porous shell structure comprising a binder and carbon; an anode comprising silicon, lithium, or a lithiated oxide; and an electrolyte separating the sulfur cathode and the anode; Including, The electrochemical cell.
13. 13. The electrochemical cell of claim 12 further comprising a current collector.
14. 13. The electrochemical cell of claim 12, wherein the current collector comprises aluminum.
15. The lithium oxide is Li x Z y O a 13. The electrochemical cell of claim 12 comprising the general formula: where Z represents a nonmetal, and x, y, and a are each greater than or equal to 1.
16. 13. The electrochemical cell of claim 12, wherein the lithiated oxide comprises lithiated silicon oxide.
17. The sulfur particles are elemental sulfur (S 8 13. The electrochemical cell of claim 12 comprising:
18. 13. The electrochemical cell of claim 12, wherein the electrolyte comprises lithium bis(trifluoromethane)sulfonimide (LiTFSI), lithium hexafluorophosphate (LiPF6), or a combination thereof.
19. 13. The electrochemical cell of claim 12, further comprising an additive present in said electrochemical cell at a concentration of about 1% to about 5% by weight.
19. 20. The electrochemical cell of claim 19, wherein the additive comprises lithium nitrate.
20. 13. A battery comprising the electrochemical cell of claim 12, the battery exhibiting a capacity after about 100 charge / discharge cycles that is greater than about 70% of the capacity at the initial charge / discharge cycle.